<span>(x-2)*(x+2) = x*x + x*2 - 2*x - 2*2 </span> <span>(x-2)*(x+2) = x^2 + 2x - 2x - 4 </span> <span>(x-2)*(x+2) = x^2 - 4 </span> That's the long way to do it. You can use the difference of squares formula as a shortcut
(a-b)*(a+b) = a^2 - b^2
(x-2)(x+2) = x^2 - 2^2
<span>(x-2)(x+2) = x^2 - 4 </span> either way, the final answer is x^2 - 4
(X-2)(x+2) So use "f.o.i.l" meaning you multiply each first term, the outside terms, the inside terms and last terms, and then add. You'd get x^2-4 in this example